Burden of Oncothermia: Why Is It Special?. (26th May 2013) - Szasz, Oliver
Abstract : There are many contradictory opinions about conventional hyperthermia in oncology. The main points are the physical and technical imperfection of classical heating, as well as the limits of the natural physiological feedback of the organism. We would like to present the definitive differences between oncothermia and conventional hyperthermia, explaining the new line of problem solving in this important field of oncology.